Boron Management in Green gram (Vigna radiata L. Wilczek) under Custard Apple (Annona squamosa L.) based Agri-horti System in Semi-arid Region - Kumar, Raj; Singh, J.K.; Singh, Alok Kumar; Minz, Srishti Dipriya; Kumar, Nasam Midhun (Annals of Arid Zone, 2022)
An experiment was conducted at the Agricultural Research Farm, RGSC, BHU, Barkachha, Mirzapur (UP) on sandy clay loam soil during kharif 2016-17 to evaluate the effect of three levels of Boron (0.75, 1.50 and 2.25 kg ha-1) and foliar spray of two levels of Solubor (0.2 and 0.3%) on green gram (Vigna radiata L. Wilczek) under custard apple (Annona squamosa L.) based Agri-horti system. The growth and yield parameters were significantly affected by different levels of Boron and Solubor. Data revealed that application of Boron @ 2.25 kg ha-1 gave maximum values of growth parameters, yield attributes, grain and stover yield, harvest index as well as content and removal of N and S by green gram over rest of the levels. Similarly, the application of solubor @ 0.3% ha-1 exhibited higher in all growth parameters, yield attributes, yield, N and S content and its removal over rest of the levels. Moreover, the maximum net return (Rs. 60505 ha-1) was also observed under the application of boron (2.25 kg ha-1) along with solubor (0.3% ha-1).